The Ideal Age For Marriage in The Compilation of Islamic Law (KHI) and Psychology - Indra, Gandi Liyorba; Al Arif, M. Yasin; Zaelani, Abdul Qodir (al-'adalah, 2023)
This article discusses the ideal age for marriage which is examined from the perspective of Islamic law and psychology. The aim is to gain a broader understanding that can be used as material in drafting a better statutory provision. This research is library research which is descriptive in nature, using secondary data in the form of primary and secondary legal materials. The results showed that the age of marriage stated in Article 15 paragraph 1 of the Compilation of Islamic Law (KHI), namely the prospective husband is 19 years and the prospective wife is 16 years. is the result of the ijtihad of Indonesian scholars based on considerations for the benefit of the family and household. Such an age limit is deemed sufficient as the age of maturity to enter into a marriage. However, when viewed from the perspective of psychology, this age limit is still in the developmental period of adolescence and is still far from being of a mature age category. According to psychology, the ideal age for marriage is 21 to 25 years for women and 25 to 30 years for men. In this age range, the prospective bride and groom are considered ready to settle down, because they have full maturity, both physically and mentally, and can accept responsibility for managing the household